The Influence of Dioxolane Ring Conjugates on Biological Activities: A Review Study - Moath Kahtan Bashir; Mahmood Khudhayer Oglah; Yasser Fakri Mustafa; Ahmed Abdul-jabbar Mahmood (University of Mosul, 2023)
Background: The problem of drug side effects necessitates the design, synthesis, and development of novel therapeutic agents that possess high activity with minimal side effects. According to the structure-activity relationship, the dioxolane moiety is found in many natural therapeutic agents and plays an important role in their medical action. Synthetic dioxolane conjugates have been studied in a variety of biological fields, including cytotoxicity, antibacterial, antifungal, antiviral, antioxidant, and anti-inflammatory activity, and have demonstrated a distinct potency that encourages further research in this mode. Aim: This review highlights the most recent studies on dioxolane ring conjugates in various biological fields as a promising bioactive heterocyclic scaffold. Conclusion: The hydrogen bonding of the oxygen atoms in this heterocyclic ring with the target site may be responsible for the enhanced ligand-target interactions and improved bioactivity.